Assessing Year Four Pupils' Levels Of Proficiency In Measurement Formulae - Wong, Sing Ie (2017)
This study was designed to assess Year 4 pupils’ levels of proficiency in measurement formulae, namely in perimeter, area and volume using three multi-strand tests in measurement that were developed based on the mathematical proficiency model introduced by Kilpatrick et al. (2001). Based on the four demographic variables, namely type of school, location of school, mathematics achievement level and gender, Year 4 pupils’ levels of proficiency in measurement formulae were profiled. This study also determines if there is any significant difference in Year 4 pupils’ levels of proficiency based on the four demographic variables.